Penerapan Metode Irigasi Sprinkler (Curah Irrigation) Pada Tanaman Buah Naga Guna Mendukung Efisiensi Penggunaan Air Di PT. Kusuma Satria Dinasasri Wisatajaya - Yuvensia Ifenti; Hendrikus Darwin Beja; Yovitha Yasinta Bolly (Fakultas Pertanian Universitas Ratu Samban, 2025)
The sprinkler irrigation method is applied to dragon fruit plants to increase water use efficiency. This system is able to disribute water evenly to,plants,reduce waste, and meet plant needs optimally. The results of the application show better efficiency and increase the quality and quantity of dragon friut production, making it a sustainabel solution in modern agriculture. This MBKM internship activity was carried out at PT. Kusuma Satria Dinasasri Wisatajaya, this company is locade on JL. Abdul Gani Atas,Ngaglik sub- district, Batu sub-district,Batu city,east java province. This internship activity will be carried out for approximately 2 months strating from 17 September -14 November 2024. The method used inthis research is primary data collrction and secondary data. Primary dat was obtained directly by the author from the internhsip site and secondary data was collected through observation,interviews, documencation, literature study, consultation and report writing.